(untitled) (Journal of Human Sciences, 2021)
This study was set to investigate the Libyan students’ perception of a good teacher. In doing so, the study adopted a qualitative and quantitative design. The data was collected through an open and close-ended questionnaire. The data was then analysed manually. The findings have revealed that the teacher-student relationship, instructional competence and the teacher’s personality were considered to be important in determining the quality of a good teacher by the students understudy. The findings also revealed that the students understudy tend to view good teachers as those who are patient, confident, knowledgeable about the subject matter, respect the students, cares about the students, treat the students fairly and equally, sensitive to the students’ problems and encourage the students. These findings are believed to give teachers an idea on how their students view them which could help teacher to change/develop/improve their own style/way of teaching to suit their students’ needs and expectations.